ANALISIS KEPERCAYAAN DIRI SISWA KELAS 3 TERHADAP KEMAMPUAN MENULIS DI SDN 1 PANCASURA - Dita Sopyana; Resta Alinniah; Dea Asri Pujiasti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the relationship between self-confidence and learning enthusiasm of elementary school students through a mixed-methods approach. The primary issue addressed is the low student engagement in writing activities, triggered by a lack of self-confidence, with initial data indicating that 58.97% of students lack interest in conventional learning. The research employed an explanatory sequential design. Quantitative data were obtained through questionnaires administered to 39 third-grade students at SDN 1 Pancasura to measure self-confidence levels, while qualitative data were collected through observations and interviews with fourth-grade students to dissect the dynamics of learning enthusiasm. Quantitative results show that the majority of students fall into the